PENINGKATAN KETERAMPILAN FISIK MOTORIK HALUS ANAK MELALUI PAPER QUILLING KERTAS KOKORU PADA KELOMPOK B DI RA KALIMOSODO GEDANGAN–MALANG - Asih, Dwi Setyo; Sholichah , Norma Ita (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2020)
The increasing child's fine motor skills only requires coordination of hand and muscle movements that are done gradually. The aim is to describe the improvement of fine motor skills through kokoru paper quilling paper. Classroom Action Research (Action Research) by applying two cycles through the stages of the planning process, implementation, observation and reflection. Data collection techniques are done by interview, observation, and documentation. Results and discussion on changes in results seen at the end of the first cycle meeting with a percentage of 58.5%, cycle II with a 96% process. The increase between the two cycles with a percentage of 37.5% as an increase in fine motor skills of early childhood. This study concluded that the indicators of success in each learning process that emphasizes fine motor skills show a significant increase in the rate of change. The form of change can be seen from the creation of the work through kokoru paper quilling paper.